Improving the Productivity of Conical Mills by Using External Vibrations - Ivan S. Kartsev (Инженерные технологии и системы)
Introduction. In the context of growing demands for the grain processing efficiency, an urgent task is to increase the productivity of mill equipment. One of the key problems is the uneven feeding of grain into the milling zone. It is proposed to use external vibrations that coincide with the resonant frequency of the grain to improve the uniformity of feeding and grain orientation that can reduce the processing time. Aim of the Study. The study is aimed at determining the influence of external vibration effect on the motion dynamics and orientation of barley grain when feeding into conical mills to improve the productivity and energy efficiency of the milling process. Materials and Methods. To obtain the data necessary for the calculation, there were carried out numerical simulation, modal analysis in ANSYS, and determination of the natural frequencies of barley grain vibrations. Results. There have been found a theoretical justification. There have been derived the equations of grain motion along the vibrating surface of the loading hopper; there has been calculated the average speed of barley grain motion taking into account the external vibrational effect. Then, an experimental test was carried out with the use of a laboratory setup with a vibration motor and a measuring system. The grain milling time was compared with and without external vibration effect. The simulation showed that when exposed to vibration effect with a frequency of 4,394 Hz, the average grain speed increases from 0.70 to 0.96 m/s (an increase of 27%). The experiment confirmed a reduction in the grain lot milling time by 23.89%. There have been calculated the energy cost savings: a reduction of up to 20.96% compared to the mode without external vibration effect. Discussion and Conclusion. The results demonstrate that the use of external vibration effect synchronized with the natural frequency of grain vibrations significantly increases the mill productivity due to improved feeding and orientation of the grain material. The method has proven its energy efficiency and can used for industrial installations.